Equity, Envy and Independence of Irrelevant Alternatives - Vincenzo Denicolò (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 1996)
We show that any social choice function that always selects envy-free Pareto efficient allocations must violate Arrow's condition of independence of irrelevant alternatives.
Keywords: 330